Respiratory impairment induced by smoking in children in secondary schools. Issue 6421 (24th March 1984) - Adams, L; Lonsdale, D; Robinson, M; Rawbone, R; Guz, A
Abstract : A longitudinal study was carried out from 1975 to 1979 in a cohort of 405 secondary school children. At yearly intervals they underwent a series of tests of pulmonary function designed to monitor lung development; some of these tests are relatively sensitive indicators of early abnormalities. A self administered questionnaire provided details of smoking habits and respiratory symptoms. The prevalence of smoking increased with age; most of those smoking at 16 had already been smoking, at least experimentally, at 13. Taking up smoking was clearly associated with the early onset of cough, production of phlegm, and shortness of breath on exertion. After two years of smoking more than a few cigarettes a day the children who smoked appeared considerably less healthy than their non-smoking peers and showed some evidence of early obstruction of the airways.